Hubungan Tingkat Pengetahuan Covid 19 dengan Penggunaan Masker pada Siswa SMAN 1 Ciampel - Jini Surya Aditia; Ismawati; Adjat S Rasjad (UNISBA Press, 2023)
Abstract. Covid-19 is an infectious disease attacking the respiratory tract caused by severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2) which can cause mild to severe symptoms such as coughing, shortness of breath, and fever. The easy transmission of the virus causes faster spread and is influenced by several factors such as a lack of knowledge about Covid-19 and preventive behavior that has not been maximized. This study aims to determine the relationship between the level of student knowledge and the behavior of wearing masks at SMAN 1 Ciampel in 2022. Ciampel is a sub-district with a fairly high number of Covid-19 cases, with 917 confirmed patients in 2021. This type of research is an analytical study with the method cross-sectional. The research subjects were randomly selected sample Random Sampling in students of SMAN 1 Ciampel in 2022 and obtained 248 respondents, with an average value of knowledge of 70 in the sufficient category and an average value of behavior of 70 in the sufficient category. Analysis of the data using a test that squares with a value of 0.007 indicate that there is a significant correlation between knowledge and behavior in using masks. The conclusion of this research shows that a high level of knowledge is directly proportional to the level of behavior. After knowing about Covid-19, one can determine what to do, such as the behavior of using masks properly so that it can affect the effectiveness of the mask as personal protective equipment. Abstrak. Covid-19 adalah penyakit menular menyerang saluran pernafasan disebabkan oleh Severe Acute Respiratory Syndrome corona virus 2 (SARS-CoV-2) yang dapat menimbulkan gejala ringan hingga berat seperti batuk, sesak napas dan demam. Transmisi virus yang mudah menyebabkan penyebaran lebih cepat, dan dipengaruhi beberapa faktor seperti pengetahuan yang kurang mengenai Covid-19 dan perilaku pencegahan yang belum maksimal. Penelitian ini bertujuan untuk mengetahui hubungan tingkat pengetahuan siswa dengan perilaku penggunaan masker di SMAN 1 Ciampel pada tahun 2022. Ciampel merupakan kecamatan dengan kasus Covid-19 yang cukup tinggi yaitu terdapat 917 pasien terkonfirmasi pada tahun 2021. Jenis penelitian ini adalah studi analitik dengan metode cross sectional. Subjek penelitian dipilih secara Simple Random Sampling pada siswa SMAN 1 Ciampel tahun 2022 dan didapatkan 248 responden, dengan nilai rata-rata pengetahuan 70 termasuk kategori cukup dan nilai rata-rata perilaku 70 dengan kategori cukup. Analisis data tersebut menggunakan uji chi square dengan nilai 0,007 menunjukan bahwa terdapat korelasi yang signifikan antara pengetahuan dengan perilaku penggunaan masker. Kesimpulan hasil penelitian ini menunjukan, tingginya tingkat pengetahuan berbanding lurus dengan tingkat perilaku. Setelah mengetahui tentang Covid-19 maka seseorang dapat menentukan apa yang akan dilakukan seperti perilaku penggunaan masker dengan baik sehingga dapat mempengaruhi keefektifan masker tersebut sebagai alat pelindung diri.